Preliminary study of Morphological and Genetic Diversity on Asian Green Mussel (Perna viridis) in Santubong, Sarawak - Siti Noorhidayu, Binti Ibrahim (Universiti Malaysia Sarawak (UNIMAS), 2014)
The Asian green mussels (Perna viridis) belonging to the Family Mytilidae plays important role due to its commercial value and feeding behaviour. Up to October 2013, there is no genetic information Cytochrome Oxidase I (COI) gene of P. viridis from Malaysia deposited in the GenBank. Thus, this study aims to sequence COI gene of P. viridis collected in Santubong, Sarawak and study the morphology and genetic diversity of P. viridis sampled from Santubong based on COI gene sequences analysis. A total of 12 Asian green mussels were subjected to assesement of morphological characteristics. Detail of the colour shell, shape and range shell morphology of all samples are similar to P. viridis. Approximately 550bp COI gene had been successfully sequenced. The genetic divergence values between P. viridis in Santubong, Malaysia and China ranged from 0% to 0.3%. While genetic divergence between P. viridis and other Perna sp. ranged from 60.2% to 60.5%. The topologies of all constructed phylogenetic tree based on COI gene showed that P. viridis is monophyletic since all P. viridis were grouped together forming one clade with 100% bootstrap value. This study involved only limited samples thus could be regarded as preliminary study only.